Pterosaur integumentary structures with complex feather-like branching. Issue 1 (January 2019) - Yang, Zixiao; Jiang, Baoyu; McNamara, Maria; Kearns, Stuart; Pittman, Michael; Kaye, Thomas; Orr, Patrick; Xu, Xing; Benton, Michael
Abstract Pterosaurs were the first vertebrates to achieve true flapping flight, but in the absence of living representatives, many questions concerning their biology and lifestyle remain unresolved. Pycnofibres—the integumentary coverings of pterosaurs—are particularly enigmatic: although many reconstructions depict fur-like coverings composed of pycnofibres, their affinities and function are not fully understood. Here, we report the preservation in two anurognathid pterosaur specimens of morphologically diverse pycnofibres that show diagnostic features of feathers, including non-vaned grouped filaments and bilaterally branched filaments, hitherto considered unique to maniraptoran dinosaurs, and preserved melanosomes with diverse geometries. These findings could imply that feathers had deep evolutionary origins in ancestral archosaurs, or that these structures arose independently in pterosaurs. The presence of feather-like structures suggests that anurognathids, and potentially other pterosaurs, possessed a dense filamentous covering that probably functioned in thermoregulation, tactile sensing, signalling and aerodynamics. Microscopic and spectroscopic analyses and imaging of integumentary structures in two anurognathid pterosaurs reveal that their integuments were more like feathers (as seen in maniraptoran dinosaurs) than fur, as was previously supposed.